Food sources of macrobenthos in an estuarine seagrass habitat (Zostera noltii) as revealed by dual stable isotope signatures - Vafeiadou, Anna-Maria (2013)
Stable carbon and nitrogen isotope analysis was used to examine the resources and position of macrobenthos in an estuarine seagrass food web in two sampling moments, during summer and winter. The contribution of each food source to the carbon requirements of consumers was estimated by a mixing model. The used carbon sources were largely seagrass associated, although seagrass tissues were utilized by only few species, and equally contributed to microphytobenthos and suspended particulate organic matter. Based on isotopic data, Lucinidae bivalves have an alternative trophic pathway via symbiosis with chemoautotrophic bacteria. Resource utilization inside and adjacent to seagrass beds did not differ significantly, implying that seagrass-associated inputs extend well beyond the borders of the vegetation patches.